Realising agency: insights from participatory research with learners in a South African sexual and reproductive health programme - Coakley, Chelsea; Lee, Devyn; Pike, Carey; Myers, Laura; Hartmann, Miriam; Oduro, Asantewa; Ntlapo, Noluthando; Bekker, Linda-Gail, Youth Investigators of the Goals for Girls study (Frontiers in Public Health, 2024)
Investing in the capabilities of adolescents is essential to achieving the United Nation’s Sustainable Development Goals, which focus on realising adolescent girls and young women's (AGYW) rights to education, health, bodily autonomy and integrity, sexual and reproductive health (SRH) and well-being. Despite significant scientific and programmatic progress in understanding and responding to their unique and intersecting vulnerabilities, AGYW continue to face disproportionate risk of STIs, HIV and early pregnancy. In South Africa, increasing rates of adolescent pregnancy, persistent and disproportionate HIV infections and the syndemic interactions between negative health outcomes amongst AGYW call for urgent, tailored interventions, which stand to be improved by early and meaningful engagement of AGYW in intervention design and delivery. Comprehensive sexuality education (CSE) is a critical component of securing universal access to SRH and rights for all adolescents. School-based CSE programmes have demonstrated improvements in learners' SRH, as indicated by increased HIV knowledge, delayed sexual debut, improved self-efficacy to engage in safer sex, and reduced sexual risk behaviours. The participatory sub-study generated lessons for future implementation through collaborative methods, and provides further insight into the quantitative biomedical and socio-behavioural findings of the larger study. This study successfully employed a Youth-Participatory Action Research (YPAR) approach to augment qualitative data collection from SKILLZ participants. YPAR was firstly found to be acceptable to both the YIs and their participant peers and secondly, it could generate high-quality research data that enriched understanding of the impact of SKILLZ.